2015
DOI: 10.1007/s00044-015-1473-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel 5-[(1,2,3-triazol-4-yl)methyl]-1-methyl-3H-pyridazino[4,5-b]indol-4-one derivatives by click reaction and exploration of their anticancer activity

Abstract: A series of pyridazino [4,5-b]indole derivatives containing alkyl-, benzyl-and phenacyl-substituted 1,2,3-triazolylmethyl units was synthesized using click chemistry approach. All 30 compounds of the series were screened in vitro against four cancer cell lines, viz. breast cancer cells MDA-MB-231 and MCF 7, human primary glioblastoma U-87 and human neuroblastoma IMR-32 cell lines. Most of the compounds exhibited potent cancer cell growth inhibition activity at very low micromolar concentrations. The IC 50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…As reported, pyridazinone derivatives have a wide range of biological activity, including the anti-cancer effects [ 16 18 ]. Recently, many literatures have focused on the design and synthesis of pyridazinone derivatives to develop new compounds with higher anti-cancer efficacy and verify the potential specific target [ 19 21 ]. Some studies have demonstrated that their specific mechanisms are acting as the inhibitors for important tumor targets such as p38, PFKFB3, PARP-1, C-Met or C-Met/HDAC [ 22 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, pyridazinone derivatives have a wide range of biological activity, including the anti-cancer effects [ 16 18 ]. Recently, many literatures have focused on the design and synthesis of pyridazinone derivatives to develop new compounds with higher anti-cancer efficacy and verify the potential specific target [ 19 21 ]. Some studies have demonstrated that their specific mechanisms are acting as the inhibitors for important tumor targets such as p38, PFKFB3, PARP-1, C-Met or C-Met/HDAC [ 22 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the intriguing structures and the medicinal importance of polycyclic indole-based molecules [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], we envisioned that the amalgamation of the indole moiety [ 8 , 9 , 10 , 11 , 12 , 13 ] with the pyridazine ring [ 14 , 15 , 16 , 17 , 18 , 19 ] that potentially generates different isomeric scaffolds ( a – c ) would lead to entities endowed with either amplified or new biological activities ( Figure 1 ). A large number of reports dedicated to the synthesis of these appealing frameworks and studies on their pharmacologic activities appeared in the literature in the past few decades [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Among the heterocyclic architectures a – c , the tricyclic fused indole-pyridazine system c which can be considered to be aza-analogous (or bioisoster) of β-carboline, the unique tricyclic pyrido[3,4- b ]indole core amenable to an important family of bioactive natural products widely distributed in nature [ 30 ], has attracted our attention.…”
Section: Introductionmentioning
confidence: 99%
“…Although many of the above cited examples deal with 5 H -pyridazino[4,3- b ]indoles ( a ) [ 20 , 21 ] and 5 H -pyridazino[4,5- b ]indoles or 3 H -pyridazino[4,5- b ]indol-4(5 H )-ones ( b ) [ 22 , 23 , 24 , 25 , 26 ], the chemistry of 9 H -pyridazine[3,4- b ]indoles ( c ) [ 27 , 28 , 29 ] is much less known.…”
Section: Introductionmentioning
confidence: 99%
“…[8] In addition, indole-fused oxazinone derivatives are present in a large number of bioactive compounds and some representative members of this family are also depicted in Figure 1. For example, compound E, [9] compound F, [10] and compound G, [11] show anticancer properties. Etodolac H is used for the treatment of arthritis, [12] and oxazinoindolones I showed anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%